(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Chronic obstructive pulmonary disease (COPD) is a common chronic airway inflammatory disease. With its heterogeneity in clinical manifestations, treatment responses and prognosis, biomarkers that can predict treatment benefits and risk stratification of deterioration are very important. In recent years, many studies have reported that eosinophils are highly involved in the development of airway inflammation in COPD. The baseline blood eosinophil count(EOS) is related to the therapeutic effect of inhaled corticosteroids(ICS) and the risk of acute exacerbation in patients. The level of EOS may be affected by many factors such as geography, race, etc. In domestic clinical work, the actual reference data of EOS may not be consistent with the recommended reference threshold value in GOLD. Since there is no uniform and accurate epidemiological data on EOS in COPD patients in China, this review focuses on the research progress and controversy in the areas of EOS and COPD airway inflammation, development as biomarkers, and the role of guiding the clinical application of ICS, to discuss the setting of the critical value of EOS of Chinese COPD patients.